GEOWISATA PULAU MANADO TUA, PULAU BUNAKEN DAN PULAU SILADEN DI KAWASAN TAMAN NASIONAL BUNAKEN, KOTA MANADO, PROVINSI SULAWESI UTARA. - Djaya, Andika; Masulili, Febryanto (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2025)
ABSTRACT: Geotourism is nature tourism to invite tourists to see geological phenomena and find out how these phenomena occur around us. Packed with several other aspects, such as: geological diversity, biological diversity and cultural diversity, so that geotourism has the best development potential in supporting tourism by prioritizing the principle of protection (conservation) of nature for the sustainability of the ecosystem. This research was conducted with three methods, namely the literature study stage, the field research stage, and the geosite and geodiversity site inventory stage based on the technical guidelines for the assessment of geological heritage resources where the scoring method was proposed by J, Brilha (2016). The parameters used are the assessment of scientific values, educational values, tourism values, and the risk of degradation and added value owned by a geosite. From the results of research on the three islands, 4 geosites and geodiversity sites were found, namely, Bunaken Pyroclastic Cliffs, Contact Pyroclastic Cliffs with Bunaken Limestone, Old Manado Lava Flow, and Bunaken Reef Limestone Cliffs. In addition to these geosites, caves, other beaches that can be potential geodiversity sites. Thus the Bunaken National Park area has the potential to become a geotourism object with assessment aspects based on the quantitative value of various natural beauties and geological processes that control the formation of the geotourism object. To increase the potential of geotourism, infrastructure development and good promotional planning are needed so that it can become a leading tourist location in Manado City.